2006 39th Annual IEEE/ACM International Symposium on Microarchitecture (MICRO'06) 2006
DOI: 10.1109/micro.2006.18
|View full text |Cite
|
Sign up to set email alerts
|

Die Stacking (3D) Microarchitecture

Abstract: 3D die stacking is an exciting new technology that increases transistor density by vertically integrating two or more die with a dense, high-speed interface. The result of 3D die stacking is a significant reduction of interconnect both within a die and across dies in a system. For instance, blocks within a microprocessor can be placed vertically on multiple die to reduce block to block wire distance, latency, and power. Disparate Si technologies can also be combined in a 3D die stack, such as DRAM stacked on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
291
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 497 publications
(293 citation statements)
references
References 27 publications
2
291
0
Order By: Relevance
“…The modeling parameters and thermal constants for each layer are as described in [2,26] and reproduced in Table 3. The heat sink is placed close to the bottom Table 3.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The modeling parameters and thermal constants for each layer are as described in [2,26] and reproduced in Table 3. The heat sink is placed close to the bottom Table 3.…”
Section: Methodsmentioning
confidence: 99%
“…We execute the 3D processor at a lower voltage and frequency than the 2D baseline processor until its average peak temperature matches that of the baseline. Similar to the methodology in [2], we assume that voltage and frequency scale linearly for the voltage ranges considered here. We observed that a 3D processor with a 7 W checker (15 W checker) operating at a frequency of 1.9 GHz (1.8 GHz) has the same thermal characteristics as a 2D baseline processor operating at a frequency of 2 GHz.…”
Section: Performancementioning
confidence: 99%
“…Coherence between L1 and L2 caches is kept using a directory-based MOESI protocol. We assume 3D-stacking [11], and therefore, each node in the CMP has a memory controller. Regarding the on-chip network, we use a mesh topology which has all the links among nodes of the same size and width.…”
Section: Case Of Studymentioning
confidence: 99%
“…Recently, this kind of exploration is used for performance improvement by Black et.al. in [29]. However this study is limited to single-layer blocks.…”
Section: Performance Estimationmentioning
confidence: 99%